A study of the wear mechanisms of disk and shoe brake pads. (October 2015) - Laguna-Camacho, J.R.; Juárez-Morales, G.; Calderón-Ramón, C.; Velázquez-Martínez, V.; Hernández-Romero, I.; Méndez-Méndez, J.V.; Vite-Torres, M.
Highlights: Wear mechanisms on disk and shoe brake pads identified after real service. Characterization techniques such as SEM, EDS and AFM employed. Wear processes as sliding and abrasion produced third-body layers in the disk pad. Fatigue cracks and pits were observed on the shoe pads after real service. AFM showed the surfaces of both brake pads, before and after real service. Abstract: In the present work, a study and description of the wear mechanisms implied in disk and shoe pads (bodies) was presented. These were subjected to real service, roughly 8 months, in a city as Poza Rica in Mexico that is extremely warm (high temperatures between 40 °C and 50 °C), which lead to cause a more rapid wear process. The surface characteristics and the differences in the wear modes of the brake pads were shown. These observations allowed concluding that high sliding and abrasion wear deformed the disk pad surfaces leading to form third body layers, friction layers and friction films that determined the friction behavior of the automotive brakes. In relation to the shoe pads, although sliding wear occurred, the wear mechanism more evident was the formation of fatigue cracks due to the impact actions with the drum (counter-body). The images of the unworn and worn surfaces were obtained by using scanning electron microscopy (SEM). In addition, energy-dispersive X-ray spectroscopy (EDS) was employed to obtain the chemical analysis of unworn and worn pads. Finally, Atomic Force Microscopy (AFM) was utilized to have a perspective of the degradation of the worn pads.